Psychosomatic aspects of motion and seasickness - a literature review and evaluation according to QUADAS-2 tool - Podstawka, Zuzanna; Zieliński, Grzegorz; Gawda, Piotr (Journal of Education, Health and Sport, 2020)
Background Greater affluence and cheaper travelling have enabled a rapid increase in the number of people travelling around the world. About two thirds of travelers have experienced symptoms of motion sickness at least once. A known type of motion sickness is sea sickness. In extreme situations can concern as many as 60 % of even an experienced crew and as many as from 60 to 90% inexperienced sailors. Growing number research of is linking this disease to a psychosomatic reaction. The aim of the study was to review the literature on psychosomatic aspects of motion and seasickness and to evaluate them according to QUADAS-2 tool. Materials and methods Materials for this literature review were found by two authors using PubMed, ResearchGate, and Google Scholar databases. A combination of the keywords „seasickness”, „motion sickness”, „psychology” (according to Medical Subjects Headings- MeSH) was used to identify relevant studies. Finally, five publications were qualified for literature review. Each publication qualified for review was evaluated in accordance with the Quality Assessment Tool for Diagnostic Accuracy Testing (QUADAS-2). Results The knowledge gained from 4 studies indicated that there is a relationship between the symptoms of motion- and seasickness and psychological conditions, and one of them suggests that these relationships are small. According to the QUADAS-2 tool, there is low possibility of making mistakes in patient selection and test indexes, but the studies are at risk of bias in terms of time and flow. Conclusions Considering all the reports on this subject, it is suggested that psychological factors related to personality traits, self-control and neuroticism have a significant impact on motion sickness, including seasickness. It is recommended to conduct further research on the subject.